Monitoring the patient–ventilator asynchrony during non-invasive ventilation - Longhini, Federico; Bruni, Andrea; Garofalo, Eugenio; Tutino, Simona; Vetrugno, Luigi; Navalesi, Paolo; De Robertis, Edoardo; Cammarota, Gianmaria (Frontiers in Medicine, 2023)
Patient–ventilator asynchrony is a major issue during non-invasive ventilation and may lead to discomfort and treatment failure. Therefore, the identification and prompt management of asynchronies are of paramount importance during non-invasive ventilation (NIV), in both pediatric and adult populations. In this review, we first define the different forms of asynchronies, their classification, and the method of quantification. We, therefore, describe the technique to properly detect patient–ventilator asynchronies during NIV in pediatric and adult patients with acute respiratory failure, separately. Then, we describe the actions that can be implemented in an attempt to reduce the occurrence of asynchronies, including the use of non-conventional modes of ventilation. In the end, we analyzed what the literature reports on the impact of asynchronies on the clinical outcomes of infants, children, and adults.